Research Progress on Mitochondrial Protective Effects of Plant Polyphenols - Yuxin LIU; Ru JIA; Annan WU; Quanhong LI; Xiaojun LIAO; Jing ZHAO (Shipin gongye ke-ji)
Plant polyphenols are a class of natural phenolic compounds widely found in nature, known for their significant biological activities such as antioxidant, anti-inflammatory, anti-tumor and cardiovascular and cerebrovascular protective effects. Mitochondria are the energy factories of cells, and their dysfunctions are closely related to human metabolic abnormalities and the development of diseases. In recent years, the role of plant polyphenols in protecting mitochondrial function has received widespread attention. This review summarizes the classification and sources of plant polyphenols, and focuses on their mitochondrial protective effects, which include regulating the levels of mitochondrial reactive oxygen species as well as calcium ions, increasing the activity of mitochondrial respiratory chain enzymes, and regulating mitochondrial fission, fusion and autophagy. These properties with the potential roles contribute to treat diabetes mellitus, lung diseases, fatty liver disease, cardiovascular diseases, and neurodegenerative diseases associated with mitochondrial dysfunction. By summarizing the protective effects of polyphenols on mitochondria, this review will be beneficial for researchers to explore the conformational relationship between polyphenols and the regulation of mitochondrial function and to analyze the molecular mechanisms involved. The review not only provides a scientific basis for the development of novel plant-derived functional ingredients, but also provides a new perspective for dietary intervention on human diseases.